Upaya Peningkatan Kemampuan Analisis Melalui Model Pembelajaran Kooperatif Tipe TAI (Team Assisted Individualization) pada Mata Pelajaran Fiqih Siswa Kelas VIII MTs Nurul Huda - Mumahhad Aidil Nur; Muhammad Supawi; Halimatussakdiah Halimatussakdiah (Reslaj : Religion Education Social Laa Roiba Journal, 2020)
Efforts to Improve Analytical Ability Through Cooperative Learning Model Type TAI (Team Assisted Individualization) in Fiqh Subjects for Class VIII MTs Nurul Huda.The background of this research is that based on the identification carried out by the researchers at the research location, namely: the Fiqh learning process in the classroom still uses the classical method where learning is centered on the teacher, so that learning at MTs Nurul Huda on Fiqh subjects is one-way, more teacher-centered so that students become passive. The objectives of this research are: To determine the analytical ability in fiqh subjects in class VIII MTs Nurul Huda before and after using the Cooperative Learning Model Type TAI (Team Assisted Individualization). This research was conducted in the form of classroom action research. According to the type of research chosen, namely classroom action research, this research uses an action research model in the form of a spiral and from one cycle to the next. The results of this study are: Increasing student learning outcomes using the Cooperative Learning Model Type TAI (Team Assisted Individualization) is also seen from the increase in the average percentage of each indicator of analytical ability from cycle I to cycle II, which is as follows from the results of research on learning cycle II This shows an increase in results compared to the improvement in previous learning (cycle I). The average classical completeness is 87.5% so that classical completeness has been achieved because the completeness is more than 80%..